Growth, biochemical response and liver health of juvenile barramundi (Lates calcarifer) fed fermented and non-fermented tuna hydrolysate as fishmeal protein replacement ingredients - Siddik, Muhammad A.B.; Howieson, Janet; Ilham, Ilham; Fotedar, Ravi (PeerJ, 2018)
Conventional aquaculture feed materials available in Australia are expensive, which has prompted the search for alternatives that would be cost-effective and locally available. The present study was undertaken in order to maximize the use of a tuna hydrolysate (TH), which was produced locally from the tuna-processing discards. The growth performance, biochemical status, antioxidant capacity and liver health of juvenile barramundi (Lates calcarifer) were assessed. Two series of isonitrogenous and isocaloric diets labelled as TH50, TH75 (non-fermented tuna hydrolysate) and FTH50, FTH75 (fermented tuna hydrolysate) were formulated to replace FM at 50% and 75%, respectively. A basal diet without the TH supplementation was used as a control. The experimental diets were fed to the triplicate groups of fish three times a day for 56 days. The results of the experiment revealed that fish fed on both fermented and non-fermented TH-containing diets significantly reduced (p < 0.05) the final body weight, weight gain and specific growth rate compared to the control. The highest apparent digestibility coefficients for dry matter, protein and lipid were obtained in the control group, and decreased with the increasing level of TH in the diets. However, the whole-body proximate compositions and the blood biochemical indices of fish were not affected by the TH inclusion in the diets. The fish fed on TH diets of TH50, FTH50 and TH75 exhibited reduced (p < 0.05) glutathione peroxidase (GPx) activity compared to the control; whereas the FTH75 exhibited no difference with the control. The excessive inclusion of TH in the diets of TH75 and FTH75 resulted in cytoplasmic vacuolization, with an increased amount of lipid accumulation, and necrosis in the liver tissue. These results indicated that the replacement of the FM protein with TH at 50% and 75% inclusion levels negatively affected the growth performance, feed utilization, and digestibility in juvenile barramundi; and it also increased the potential risk of hepatic failure in the fish. Further investigation is, therefore, required in order to optimize the TH levels in the fish diets which would be suitable for the growth of fish, as well as for maintaining the enhanced biochemical response in juvenile barramundi.
Keywords: Barramundi; GPx activity; Fermentation; Tuna hydrolysate; Biochemical response